Perceived employability, job crafting and career success: The case of young professionals in Vietnam - Thi Ngoan, Dinh (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This study aimed to investigate whether career competencies could enhance young professionals’ perceived employability via job crafting and career success. 1008 respondents answered an online survey with 957 valid answers. Partial least square structural equation modeling was used and the results of the study were significant. First, career competencies directly affect perceived internal and external employability with the stronger effect on the latter. Second, career success partially mediates the relationship between career competencies and perceived internal employability. Third, job crafting partially mediates the relationship between career competencies and perceived employability. The study extends the previous literature on employability to a personal perspective with the effects of personal resources through personal adaptation and success leading to HR management indications.